2019
DOI: 10.1038/s41598-019-54441-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of magnetic resonance imaging in the preoperative evaluation of anal fistulas

Abstract: This study aimed to determine the role of magnetic resonance imaging (MRI) in diagnosing and describing the characteristics of fistula-in-ano, and the agreement between MRI and operative findings. We conducted a retrospective study in 367 patients with fistula-in-ano who were diagnosed and had an operation at the University Medical Center between January 2016 and January 2018. MRI findings were evaluated and compared with surgical findings using the kappa coefficient (k) method. 367 patients (327 male and 40 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 15 publications
4
20
1
4
Order By: Relevance
“…The key determinant of success in fistula surgery is the radiological assessment. The availability of MRI and transrectal ultrasound (TRUS) have greatly enhanced the understanding of anal fistulas[ 27 ]. The importance of preoperative assessment of the fistula with MRI or TRUS cannot be overemphasized.…”
Section: Discussionmentioning
confidence: 99%
“…The key determinant of success in fistula surgery is the radiological assessment. The availability of MRI and transrectal ultrasound (TRUS) have greatly enhanced the understanding of anal fistulas[ 27 ]. The importance of preoperative assessment of the fistula with MRI or TRUS cannot be overemphasized.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity for abscesses were 100%. A simultaneous comparison of T2W TSE (turbo spin echo) and post-contrast T1W TSE sequences revealed the latter to be more sensitive but the former to be more specific for internal opening and secondary tracks [53]. In another prospective study, apart from showing a high sensitivity and specificity for diagnosing fistula track (98.6% and 99.7%) and identification of internal opening (97.7% and 98.6%), MRI also added significant information in 46.7% cases regarding parameters of complexity, thus establishing its role as an important pre-operative imaging tool for fistula-in-ano [54].…”
Section: Discussionmentioning
confidence: 99%
“…Combined T2W TSE and postcontrast fat sat T1W TSE sequences had high sensitivity (96.6% and 98.4%, respectively) and specificity (92.6% and 81.5%, respectively) for depicting internal openings and secondary tracts, and postcontrast T1 FS TSE sequence was 100% accurate in delineating abscesses. 11 In our study, we compared plain MRI study including axial T1W, axial and coronal oblique T2 W and T2 FS images with postcontrast axial, coronal, and sagittal T1 FS TSE images. We found that T2 and T2FS images were sufficient to make the diagnosis of fistulas as well as their complications in all 30 patients (100%).…”
Section: Discussionmentioning
confidence: 99%